ISLAMIC BUSINESS TECHNOLOGY BASE INCUBATOR AND MICRO SMALL ENTERPRISES CENTER (IBTI–MSEC) SEBAGAI LABORATORIUM ENTREPRENEUR ISLAM - Eka Tresna Gumelar (Jurnal Manajemen Bisnis Performa, 2016)
A country primary socio economic goal is to improve the quality life of their citizens. The competitiveness of the economic must be raised, opportunities that empower people to earn sustainable incomes must be created, and problem affecting the population and environmental degradation must be alleviated. Based on current condition where fewer jobs, the number of graduated unemployment was increased 51% from last year and the development of entrepreneurship among youth is getting better. For that case, we need an institution for students to practice the business and transform their ideas into start-up business.